Pharmacokinetic Behaviour of Antithrombin III Following Intravenous Infusion in Healthy Volunteers - Marzo, Antonio; Ceppi-Monti, Nunzia; Giusti, Andrea; Abbiati, Gianalfredo; Maddalena, Parenti (Arzneimittelforschung, 2002)
Antithrombin III (CAS 52014-67-2) is produced from plasma of healthy donors and is purified from any detectable agent of transmissible infection. This drug is used in therapy by i.v. route to manage acute thrombotic episodes and to treat patients suffering from its deficiency.The present trial was conducted with the aim to evaluate the pharmacokinetics and the safety of a new preparation of antithrombin III, which in the purification procedure has included a nanofiltration step to increase the safety against the transmission of any agent of infection.The trial was conducted in twelve healthy volunteers of either sex. All the ethics procedures were fully respected, namely the approval from Ethics Committee, the notification to the central regulatory authority, the approval of consent form in writing. Volunteers were hospitalized about 36 h before drug treatment. The baseline situation was investigated throughout the day before the treatment (day −1). On day 1, the drug was infused i.v. for 20 min. Twenty blood samples were drawn from each volunteer, in baseline situation, during and after the infusion. Functional antithrombin III, antithrombin III antigen, prothrombin time, partial thromboplastin time were evaluated in all plasma samples. Both functional antithrombin III and antithrombin III antigen produced well defined plasma concentration-time profiles after the infusion, which allowed net values of these two analytes to be obtained subtracting baseline from post-infusion concentrations. Net pharmacokinetic parameters of functional antithrombin III and antithrombin III antigen proved to be almost superimposable. A comparison of data obtained in this trial on healthy volunteers with those previously obtained by other authors on target population demonstrates similar and fully comparable results.The authors conclude that the nano-filtration step neither affects at all the pharmacokinetics/pharmacodynamics nor the safety of the formulation investigated.
Keywords: Antithrombin, antithrombin III, antithrombin III antigen, functional antithrombin III; healthy volunteers, nanofil-tration purification, pharmacokinetics; CAS 52014-67-2